The use of cooperative learning techniques in teaching literature in English among secondary teachers in Kuching and Kota Samarahan divisions - Benedict Saran, Ingkon. (Universiti Malaysia Sarawak (UNIMAS), 2005)
This study sought to find out the use of Cooperative Learning techniques in the teaching of literature in English among secondary teachers in Kuching and Kota Samarahan divisions. In realizing the importance of the English language, literature is one of the components in the syllabus to promote the language and to enhance students in their learning, which requires students to analyse and evaluate certain issues in the literary texts. Thus, teaching needs to be fun and interesting to motivate them to learn. 1bis study is aimed at determining the practice of Cooperative Learning techniques in the teaching of literature in English and to find out teachers' own perspective on how they feel toward the use of cooperative we shall know how the students response to the use of these techniques in teaching and learning process. The study focuses on the types of cooperative learning techniques that are familiar to teachers, the problems that the teachers faced and how they solve the problems in line with the usage of cooperative learning techniques. 200 questionnaires were distributed to English teachers involving 40 different schools in the divisions and only 160 teachers were able to submit their questionnaires. A selected number of teachers were also interviewed. The results showed that a majority of these teachers did not receive their training from the experts but indirectly received the training through in-house training. However, the teachers viewed cooperative learning techniques very positively in promoting the teaching of literature in English.